2021
DOI: 10.3390/fermentation7020081
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Oil Palm Empty Fruit Bunch Hydrolysate

Abstract: Malaysia is the second largest palm oil producer and exporter globally. When crude palm oil is produced in both plantations and oil processing mills, a large amount of oil palm empty fruit bunch (OPEFB) is simultaneously produced as a waste product. Here, we describe the preparation of hydrolysate from OPEFB. After OPEFB was hydrothermally treated at 180–200 °C, the resultant liquid phase was subjected to high-performance liquid chromatography analysis, while the solid phase was used for acidic and enzymatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A similar increasing trend was observed for cellobiose, arabinose, galactose, and mannose after SCW pre-treatment. Likewise, Akita et al (2021) reported an increase in the concentration of glucose, cellobiose and mannose in the liquid fraction of pretreated EFB along with the increasing temperature. Meanwhile, xylose composition was not detected at a lower temperature.…”
Section: P R E S Smentioning
confidence: 82%
“…A similar increasing trend was observed for cellobiose, arabinose, galactose, and mannose after SCW pre-treatment. Likewise, Akita et al (2021) reported an increase in the concentration of glucose, cellobiose and mannose in the liquid fraction of pretreated EFB along with the increasing temperature. Meanwhile, xylose composition was not detected at a lower temperature.…”
Section: P R E S Smentioning
confidence: 82%
“…for 3 days at 50 • C in an incubator (SLI-700; EYELA, Tokyo, Japan), the dried samples were milled using a cutter mill (ABSOLUTE3; Osaka Chemical, Osaka, Japan), yielding a powder (particle size: 100-200 µm). On the basis of the findings of our previous study [21], the hydrothermal treatment of the powder was carried out. Briefly, 10 g of the powder was placed in an autoclave with 100 mL water for 30 min at 130 • C, and the resulting hydrothermally treated samples were used as the initial raw material for enzymatic hydrolysis.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…Humic acid producing microorganisms have been isolated from soil, the marine environment waste volatile substances (Muthumariet al, 2016), palm-oil mill effluent, (Jagtap andChobade, 2015). The present study addresses the dual challenges of agricultural waste management and soil health improvement by focusing on the isolation, identification, and screening of humic acid-producing fungi from the soil environment of Oil Palm EFB waste (Akita et al, 2021).…”
Section: E-issn: 2814 -1822; P-issn: 2616 -0668mentioning
confidence: 99%